FIGURASI النسآء/AL-NISĀ’/ DALAM MEDIA MASSA ARAB BBC NEWS ARABIC (TINJAUAN SEMANTIK PROSODI) - Annisa Khairunnisa; Mardjoko Idris; Reflinaldi Reflinaldi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2025)
Women's issues in online discourse are increasingly urgent to study. This is because more and more narratives that ruminate on women's problems are more complex and sentimental, because the language space is getting wider (cyberspace). Therefore, it is important to examine the figuration of النسآء/al-Nisā'/ as a diction that represents “women”, specifically in the Arabic mass media BBC News Arabic with a prosodic semantic approach. The aim is to reveal the figuration of women clearly and become a reference for the public to respond to women's issues wisely, even responsively. The data of this research are keywords النسآء/al-Nisā'/ and relevant lingual units. The data source is the BBC News Arabic mass media site in the شؤون المرأة column (https://www.bbc.com/arabic/topics/c404vr23qydt) during January-October 2023. The data collection method is by the computerized process of LanscBox and Antcont software. Then it was analyzed with John Sinclair's perspective prosodic semantic approach through collocation and concordance. The results showed that from 340 news files during January-October 2023, the words with the highest frequency of 20 tended to portray women in negative values, intimidating relationships, and subordination. Both in the position as subject and object, which tends to be reflected in the situation of Middle Eastern women.